Pengaruh Pelatihan dan Disiplin Kerja terhadap Prestasi Kerja Karyawan - Allail, Rifal; Sumiyati, Sumiyati; Purnama, Ridwan (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2017)
The purpose of this study was to determine how much influence the training on work performance, work discipline on work performance and training and work discipline on employee work performance The type of research used was descriptive, verification, with a total sample of 80 employees. The data analysis technique used is path analysis The findings from the research on hypothesis testing can be seen that training and work discipline have a positive influence / large category on employee work performance. The originality of this research is the difference found in the object of research, the period of research, the measurement tools and the results of the study.